HUBUNGAN KUALITAS TIDUR DENGAN PRESTASI BELAJAR PADA SISWA PENGGUNA APLIKASI TIKTOK DI SMA NEGERI 3 NABIRE - Selmi Belastrik Mangampa; Dewita Karema Sarajar (LPSDI Bina Patria, 2025)
This study aims to analyze the relationship between sleep quality and academic achievement among TikTok users at SMA Negeri 3 Nabire. A quantitative approach with a correlational design was employed. The sample consisted of 91 eleventh-grade students selected through purposive sampling. Sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI), while academic achievement was assessed based on report card grades. The results indicated that most students had poor sleep quality (87.9%), yet their academic achievement fell in the moderate category (95.6%). Correlation analysis revealed a positive relationship between sleep quality and academic achievement (r = 0.084), but this was not statistically significant (p > 0.05). These findings suggest that sleep quality is not the primary factor affecting students' academic achievement. The study recommends schools and parents to monitor students' social media usage and promote better sleep quality to support optimal academic performance.